STRATEGI PEMBELAJARAN INOVATIF: PENERAPAN GEOGEBRA DALAM MATERI BANGUN RUANG SISI DATAR - Agustin, Meily; Efriani, Arvin; Komarudin, Komarudin (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
Math is considered a scary subject for most students which makes them unprepared to learn, one of which is on the material of flat-sided spaces which in this case can have a negative impact on the quality of learning. For this reason, it is necessary to have an activity that can encourage students to pay more attention and be able to understand the material more thoroughly. This opens up opportunities for researchers to conduct research using teaching materials in the form of learning videos assisted by Geogebra software and then given a test to see the effectiveness of the media used. This study aims to describe innovative learning strategies using YouTube and Geogebra learning videos in learning flat-sided space building material for junior high school students. This learning method is designed to improve understanding of geometry concepts and facilitate student engagement through visual and interactive approaches. This research was conducted using descriptive qualitative method, where data were collected through tests using teaching materials. The data processing technique obtained was by using Microsoft Excel. This research was conducted in one of the public junior high schools in Palembang in April 2024 involving students of grade VIII. The results showed that the success rate of the implemented learning strategy was satisfactory as evidenced by the evaluation of learning through Google Form with a high percentage of student learning outcomes, namely 78.18182% on multiple choice indicators and 75.75758% on essay indicators, which means overall success.